Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1978977
|View full text |Cite
|
Sign up to set email alerts
|

An open, social microcalender for the enterprise

Abstract: We present the system design and rational for a novel social microcalendar called Timely. Our system has been inspired by previous research on calendaring and popular social network applications, in particular microblogging. Timely provides an open, social space for enterprise users to share their events, socialize, and discover what else is going on in their network and beyond. A detailed analysis of the events shared by users during the site's first 47 days reveals that users willingly share their time commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…One of their downsides is that users need to ensure that all their plans are captured in their calendars. Moreover, they need to explicitly allow others to access their schedules [14] and by doing so, users automatically disclose personal availability patterns [24]. Although most systems enable users to hide any detailed information (e.g., the occasion of an event) researchers have raised concerns over people's privacy [24].…”
Section: Groupware Calendars and Event Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…One of their downsides is that users need to ensure that all their plans are captured in their calendars. Moreover, they need to explicitly allow others to access their schedules [14] and by doing so, users automatically disclose personal availability patterns [24]. Although most systems enable users to hide any detailed information (e.g., the occasion of an event) researchers have raised concerns over people's privacy [24].…”
Section: Groupware Calendars and Event Schedulingmentioning
confidence: 99%
“…Palen [35,36] conducted a study of the use of groupware calendars at Sun Microsystems, and found that users were willing to share information about their availabilities if it benefited the scheduling process within their group. Geyer et al [14] investigated the use of a social calendar that combined calendaring and microblogging within IBM. Similarly to Palen's findings, they concluded that users were willing to share most of their availability information within the enterprise.…”
Section: Groupware Calendars and Event Schedulingmentioning
confidence: 99%
“…Our Suggestions feature was built as an extension to a novel social calendaring site called "Timely" [10]. The design of Timely is based on the social infrastructure underlying micro-blogging sites like Twitter.…”
Section: Timelymentioning
confidence: 99%
“…During the first 6 weeks of deploying Timely, more than 2,000 events were shared by employees ranging from customer meetings to personal deadlines. See [10] for a more detailed analysis of the site.…”
Section: Timelymentioning
confidence: 99%
“…It has moved contents such as photos, videos and bookmarks, from users' devices to online sites [3]. Those uploaded contents, like photos, videos, can be associated to one's life activities.…”
Section: Event Socialization -Motivationmentioning
confidence: 99%